Gender-based occupational segregation and gender earnings differentials across quantiles in Malaysia - Wan Zainal Abidin, Wan Liyana Mariah (2016)
One of the most stylized facts in labour economics is that women receive lower earnings as compared to men. The general objective of this research is to examine the issues of gender inequality in the labour market in Malaysia across time.Using unpublished secondary data sources of Labour Force Survey (LFS) and Household Income Survey (HIS) for 2004, 2009 and 2012, this research employs a combination of different methods to address these issues in depth. The main findings from this research may be summarized as follows. Firstly, the Duncan Dissimilarity Index and OLS regression are used to address the first objective which is to examine the level of occupational gender segregation and its determinants across time. It is found that the level of occupational segregation had worsened in 2012 as compared to the period of 2004 and 2009. Henceforth, this denotes that more male and female employees were needed to change occupations in order to equalize the occupational distribution for both gender groups within the period. Female were largely concentrated in professions such as teaching professionals and office clerks. Meanwhile, male largely worked as science and engineering professionals. From policy stance, incentive in the form of scholarships should be provided for female to motive them to enroll in the science and technical courses at the tertiary level. This would be able to reduce the extent of occupational segregation in Malaysia. Secondly, the Fortin and Huberman (2002)decomposition method is utilized to attempt the second objective which is to analyze whether the portion of gender earnings differentials is due to gender differences in occupational distribution or within occupational groups; or both, across time. Despite female educational attainment improving, they experienced lower earnings as compared to their male counterpart in most of the occupational categories within the period. Therefore, whilst vertical inter-occupational segregation had improved across time due to higher educational attainment by female which leads them to enter the male-dominated occupations, nonetheless, they remain at the lower hierarchical level within the particular occupation group. This reflects the vertical intra-occupational segregation. Furthermore, the horizontal segregation which denotes the gender attitude of what supposed to be female jobs and male jobs persist throughout the period of 2004, 2009 and 2012. To overcome this problem, it is proposed that structural evaluation technique is implemented at the office in the form of test performance,number of projects completed and revenue creation for the organization to avoid the stereotype decision making amongst the employers pertaining to employees’contribution to the company. Thirdly, the quantile regression method is used to address the third objective which is to evaluate the extent of gender earnings differentials across the earnings distribution across time, whether the glass ceiling or sticky floor exists. Glass ceiling and sticky floor exist in the Malaysia labour market in 2004, 2009 and 2012. However, the impact of sticky floor is greater than the glass ceiling.Furthermore, it is observed that the sticky floor effect had increased within the three periods. Simultaneously, the glass ceiling effect had increased across time. Therefore, it is suggested that the female decision making should be further enhanced to overcome the problem of glass ceiling in the labour market and implementation of the minimum wage policy should be enforced.